Legislative Commentary: An Analysis of Kansas Due Process Hearings 1977-1992 Support for Special Education Inclusion - Jane Adams (Educational Considerations, 1993)
School administrators are challenged to respond and meet the needs of an increasingly diverse student population, including minority, poor and disabled students. Now is the time for school administrators to apply their knowledge of the law and their understanding of democratic principles to support school diversity and lead staff in developing equity within their own classrooms.